Predictive functional assay‐based classification of PMS2 variants in Lynch syndrome. Issue 9 (28th April 2022) - Rayner, Emily; Tiersma, Yvonne; Fortuno, Cristina; van Hees‐Stuivenberg, Sandrine; Drost, Mark; Thompson, Bryony; Spurdle, Amanda B.; de Wind, Niels
Abstract: The large majority of germline alterations identified in the DNA mismatch repair (MMR) gene PMS2, a low‐penetrance gene for the cancer predisposition Lynch syndrome, represent variants of uncertain significance (VUS). The inability to classify most VUS interferes with personalized healthcare. The complete in vitro MMR activity (CIMRA) assay, that only requires sequence information on the VUS, provides a functional analysis‐based quantitative tool to improve the classification of VUS in MMR proteins. To derive a formula that translates CIMRA assay results into the odds of pathogenicity (OddsPath) for VUS in PMS2 we used a set of clinically classified PMS2 variants supplemented by inactivating variants that were generated by an in cellulo genetic screen, as proxies for cancer‐predisposing variants. Validation of this OddsPath revealed high predictive values for benign and predisposing PMS2 VUS. We conclude that the OddsPath provides an integral metric that, following the other, higher penetrance, MMR proteins MSH2, MSH6 and MLH1 can be incorporated as strong evidence type into the upcoming criteria for MMR gene VUS classification of the American College of Medical Genetics and Genomics and the Association for Molecular Pathology (ACMG/AMP). Abstract : Three‐step classification of Lynch syndrome‐associated Variants of Uncertain Significance (VUSs) in any of the DNA mismatch repair genes. (1) Protein VUSs are synthesized in vitro, based on sequence information provided by the clinical geneticist. (2) Their functional activity are assayed and quantified. (3) The odds of pathogenicity are calculated and incorporated in the final classification according to the American College of Medical Genetics and Genomics and the Association for Molecular Pathology BS3/PS3 criteria